Some aspects of regional growth and development theories - Abdul Shukor Ariffin (Universiti Kebangsaan Malaysia, 1977)
The study of regional economic is a recent phenomenon. Even though regional science has been generally accepted about twenty years ago, regional economics was still a neglected subject at that time. However, only in the past few years that study and research into the various theoretical and empirical aspects of regional economics are getting greater attention in most developed countries. This situation, however, has not yet occurred in most underdeveloped countries. Much of the economic development studies in underdeveloped countries are related to the overall national development goals and problems of those countries. But many studies seem to show that most of the development problems faced by many underdeveloped countries are a reflection of regional economic problems. It is with this point of view that this article is written. It is a 'mini survey' of some aspects of regional development and growth theories which help to explain the spatial distribution of economic activities.